The Road Ahead: eBooks, eTextbooks and Publishers' Electronic Resources - Martin, Romana (Massey University, 2012)
eBooks have now become commonplace in the community and are used on a range of mobile devicessuch as eBook readers and tablet computers. In recent years, eTextbooks accessible on a range of mobile devices have provided an alternative to heavy and expensive print-based resources. Although some institutions have decided that eTextbooks and related resources are the preferred option for their students, research does not yet indicate that students actually favor eTextbooks. There is also little evidence to support whether the additional features offered in electronic resources increase engagement or improve learning outcomes. The author describes how a review of the literature revealed current issues related to eTextbooks and their accompanying resources. This preliminary exploration will guide research to investigate whether eTextbooks and complementary resources produced by publishing companies can lead to improved learning outcomes and student engagement in a business school context.